The war in Ukraine and global food security: current challenges - Ingram, Keisha Laraine; Dankevych, Vitalii; Dankevych, Andrii; Nitsenko, Vitalii (My University, 2022)
У статті розглядається проблема глобальної продовольчої безпеки. Ми обґрунтували, що через вторгнення російських військ в Україну Росія може спричинити гуманітарну продовольчу кризу в деяких країнах світу. Тому війна Росії проти України – це також війна проти країн Близького Сходу та Північної Африки, які є основними імпортерами продовольства з України. Ми обґрунтували, що за нинішньої ситуації, а саме війни Росії проти України, дефіцит виробництва та експорту неминучий. Війна загрожує посівній. Ми встановили, що найбільше залежними від українського продовольства є Єгипет, Ємен, Індонезія, Бангладеш, Ефіопія, Ліван, Лівія, Пакистан та Ірак

The article examines the issue of global food security. We have substantiated that due to the invasion of Russian troops into Ukraine, Russia may cause humanitarian food crises in some countries around the world. That is why Russia's war against Ukraine is also a war against the countries of the Middle East and North Africa, which are the main importers of food from Ukraine. We have substantiated that given the current situation, namely Russia's war against Ukraine, a deficit in production and exports is inevitable. The war threatens the sowing campaign. We have established that the most dependent on Ukrainian food imports are Egypt, Yemen, Indonesia, Bangladesh, Ethiopia, Lebanon, Libya, Pakistan and Iraq
Keywords: global food security; invasion of russian troops; humanitarian food crises; deficit in production and exports; глобальна продовольча безпека; вторгнення російських військ; гуманітарна продовольча криза; дефіцит виробництва та експорту; економіка і право; економіка підприємства; національна безпека; економічна безпека; менеджмент; публічне управління та адміністрування; economics and law; enterprise economics; national security; economic security; management; public management and administration; кафедра економіки і права